Hubungan Antara Kadar Glukosa Darah Dan Peran Keluarga Dengan Pengendalian Diabetes Melitus Pada Pasien Diabetes Melitus Di Wilayah Kerja Puskesmas Lowu-Lowu - Darmawati Wati; Wahyuddin; Ni’ma Meilani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
The prevalence of data from the Baubau City Health Office in 2018 DM reached 594 cases, in 2019 DM reached 1.642 cases and in 2020 DM reached 1.332 cases. The prevalence of Lowu-Lowu Health Center data in 2018 reached 20 cases of DM, in 2019 DM reached 69 cases annd in 2020 it reached 33 cases and in 2021 it reached 28 cases. Blood sugar levels and the role of families in controling DM hhas the aim of controlling blood sugar levels to kep them normal. The purpose of this study was to determine the relationship between blood sugar levels and the role of the family with controlling diabetes mellitus in patients with diabetes mellitus in the working area of the Lowu-Lowu Public Health Center. This type of research is an analytic observational study with a cross sectional design. The total population in this study was 61 people, the sample was taken using the Total Sampling technique and obtained a sample of 61 people. Collecting data through primary data, namely questionnaires and secondary data. Analysis of the data used is univariate and bivariate analysis with chi square test. The results showed that there was a relationship between blood glucose levels and the control of diabetes mellitus in patients with diabetes mellitus (P Value = 0.000 <0.05) and there was no relationship between the role of the family and the control of diabetes mellitus in patients with diabetes mellitus, (P Value = 1,000 < 0.05), with the incidence of blood glucose levels and the role of the family in controlling diabetes mellitus in patients with diabetes mellitus. In the area of ​​Lowu-Lowu Health Center. The conclusion of this study is that there is a relationship between blood glucose levels and controlling diabetes mellitus and there is no relationship between the role of the family and controlling diabetes mellitus in the work area of ​​the Lowu-Lowu Public Health Center.